노인상담에 대한 노인들의 내적 지각 탐색 - CQR-M 방식을 활용하여 - 김단비(Dan-Bi Kim); 주은선(Eun-Sun Joo) (한국콘텐츠학회 논문지, 20(10), 2020)
This study explored and described how seniors cope with adversities, how they perceive the counseling and what they expect from it, including the difficulties and barriers when using psychological counseling, through direct reports of the seniors. Data was collected from 56 elderly people living in Gyeonggido through interviews. The collected data was analyzed using the CQR-M method. The result yielded 6 domains, which are the ways to deal with adversities, feelings or thoughts about counseling, motivations for counseling, why peoples mind getting counseling, expectations for counselor, expectations for counseling effect. Based on the results, the ways to increase the level of participation and consideration for counseling by the elderly are suggested including case management, the expansion of counseling areas, the formation of sincere relationships, the consideration of counseling methods with activities and the enhancement of expertise. 본 연구는 상담에 대한 지각 및 상담 서비스를 이용하는데 있어서의 장벽, 상담에 대한 기대를 노인들의 직접적인 보고를 통해 탐색하고자 하였다. 이를 위해 경기도 내에 거주하고 있는 56명의 노인들을 대상으로 면담을 통하여 자료를 수집하였다. 수집된 자료는 합의적 질적 연구 수정본(CQR-M)을 사용하여 분석하였다. 분석 결과 고민거리에 대한 대처 방법, 상담에 대한 느낌이나 생각, 상담에 대한 동기, 상담이 꺼려지는 이유, 상담자에 대한 기대, 상담효과에 대한 기대라는 6개의 영역이 도출되었다. 본 연구결과를 통해, 사례관리 및 상담영역의 확대, 진정성 있는 인간적 관계 형성, 활동을 병행한 상담 방식 고려, 전문성 강화 등 노인의 상담 숙고 및 참여도를 높이기 위한 노인상담 방안에 대해 제시하였다.